Assessing the Gap between Technology and the Environmental Sustainability of European Cities - Akande, Adeoluwa (2019)
Akande, A., Cabral, P., & Casteleyn, S. (2019). Assessing the Gap between Technology and the Environmental Sustainability of European Cities. Information Systems Frontiers, 21(3). https://doi.org/10.1007/s10796-019-09903-3